Tingkat Kebahagiaan Anak Binaan LPKA Kelas II Bengkulu: Survei - Liza Qona'ah; Anni Suprapti (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2024)
Abstract: Children are God's gifts that are entrusted to be guarded, cared for and protected. All children have the same right to a happy life. Happiness is something that every individual wants. This study aims to determine the level of happiness of children assisted by LPKA Class II Bengkulu. This research uses a descriptive quantitative approach. The data collection method in this study used a questionnaire. A total of 40 foster children were selected as simple random sampling respondents, which is the simplest sampling procedure carried out fairly, meaning that each unit has the same opportunity to be selected. The measuring instrument used to measure the level of happiness is the Oxford Happiness Questionnaire (OHQ). Based on the data obtained, 10% of foster children have happiness in the low category, 17% in the high category and 73% are in the medium category. The foster children of LPKA Class II Bengkulu have happiness in the medium category. The happiness of foster children is almost completely fulfilled, but there are several aspects that are still in the low category, namely aspects of physical fitness, satisfaction with self and satisfaction with life.